Intraoral epidermoid cyst with extensive elastofibromatous changes: an unusual finding - Silveira, Heitor Albergoni [UNESP]; Almeida, Luciana Yamamoto; Dominguete, Matheus Henrique Lopes; Graciano, Kamila Prado Pereira; Bufalino, Andreia [UNESP]; León, Jorge Esquiche (Springer Nature, 2019)
Introduction: Epidermoid cysts (ECs) are rare and occur in the head and neck regions with an incidence from 1.6 to 7% of all cysts. In the oral cavity, approximately 80 ECs have been reported, representing less than 0.01% of all cysts. Case report: We report a case of a 26-year-old man who developed a large EC in the midline floor of the mouth causing nodular swelling in the submental region and speech and swallowing difficulties. The lesion was surgically excised by intraoral approach and microscopically revealed an EC associated with extensive elastofibromatous changes in the cystic capsule. Conclusion: Oral EC with extensive elastofibromatous changes is a finding extremely rare. The meaning of this finding is unknown, but a traumatic origin or deposit disorder of elastic fibers is suggested. To the best of our knowledge, intraoral EC with elastofibromatous changes has not been reported to date.
Keywords: Elastic tissue; Elastofibromatous changes; Epidermoid cyst; Floor of the mouth; Oral cyst